2018
DOI: 10.2135/cropsci2017.07.0447
|View full text |Cite
|
Sign up to set email alerts
|

Defoliation Strategies in Pastures Submitted to Intermittent Stocking Method: Underlying Mechanisms Buffering Forage Accumulation over a Range of Grazing Heights

Abstract: For continuously stocked pastures, net forage accumulation is thought to be relatively unaffected across a rather large range of canopy‐based management targets. It is not known whether this is also characteristic of intermittently stocked canopies, and if so, the underlying mechanisms have not been well delineated. We hypothesized that initiation of grazing when canopy heights are shorter than heights corresponding to the critical leaf area index, associated with a moderate intensity of defoliation, do not re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
1
16

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 50 publications
6
44
1
16
Order By: Relevance
“…However, that cannot be interpreted as advantageous in terms of forage production, since the forage accumulation was equivalent in pastures managed between 15-25 cm (Sbrissia et al, 2018) and the values were similar to those observed in literature (García, Islam, Clark, & Martin, 2014;Swanepoel, Habig, Preez, Snyman, & Botha, 2017). The morphological composition of the grazing layer was similar among treatments, and the average values for leaves and stems proportion were 85% and 7% of DM, respectively.…”
Section: Experiments IIsupporting
confidence: 75%
“…However, that cannot be interpreted as advantageous in terms of forage production, since the forage accumulation was equivalent in pastures managed between 15-25 cm (Sbrissia et al, 2018) and the values were similar to those observed in literature (García, Islam, Clark, & Martin, 2014;Swanepoel, Habig, Preez, Snyman, & Botha, 2017). The morphological composition of the grazing layer was similar among treatments, and the average values for leaves and stems proportion were 85% and 7% of DM, respectively.…”
Section: Experiments IIsupporting
confidence: 75%
“…However, the higher-tiller birth rates observed in lower-height pastures were also associated with the lower-tiller survival rates. This higher mortality in the lower treatment can be explained by the greater pull over of tillers resulting from the higher-grazing intensity, which was also observed by Sbrissia et al (2018), in their work on kikuyu grass pastures. The population stability index allows of an integrated analysis of population changes, by considering the birth and survival rates of tillers together (Bahmani et al, 2003).…”
Section: Resultssupporting
confidence: 56%
“…At the same time, the decline in vegetation vigor in degraded grasslands is also reflected in the decrease of the canopy leaf area index. This is highly relevant, since the leaf area index is one of the main controllers of the primary production through its role in the photosynthesis [69][70][71]. On the other hand, the decrease in vigor of the vegetation could be accompanied by the substitution of high forage quality species for low forage quality ones [8,31,35,67].…”
Section: Energy Fluxmentioning
confidence: 99%